2017
DOI: 10.1111/jebm.12269
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility of lung cancer in Chinese population: An overview of systematic reviews and meta‐analyses

Abstract: The current study supports the genetic risk factors of lung cancer for Chinese are more likely to be variants from genes that contribute to the etiology of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…of Tuina (published during 2013-2017) was undertaken to assess the methodology and reporting quality based on AMSTAR (A MeaSurement Tool to Assess systematic Reviews) 2 and PRISMA checklists. 20 The results of this study showed that all SRs were rated as very low quality according to AMSTAR 2, while identified several reporting deficiencies in the PRISMA items (e.g., item 5, 6, and 23). Moreover, in our latest survey of 2447 randomized controlled trials (RCTs) of massage (from 1975 to 2020), we found that the average reporting compliance rates of the CONSORT (Consolidated Standards of Reporting Trials),…”
Section: Introductionmentioning
confidence: 77%
“…of Tuina (published during 2013-2017) was undertaken to assess the methodology and reporting quality based on AMSTAR (A MeaSurement Tool to Assess systematic Reviews) 2 and PRISMA checklists. 20 The results of this study showed that all SRs were rated as very low quality according to AMSTAR 2, while identified several reporting deficiencies in the PRISMA items (e.g., item 5, 6, and 23). Moreover, in our latest survey of 2447 randomized controlled trials (RCTs) of massage (from 1975 to 2020), we found that the average reporting compliance rates of the CONSORT (Consolidated Standards of Reporting Trials),…”
Section: Introductionmentioning
confidence: 77%
“…According to the different detection objects, there are many detection methods: ARMS, NGS, ddPCR, and FISH are targeted at DNA; RNA was targeted by RNA-Seq and RT-PCR, and IHC for protein. If the amount of tumor tissue is too small or unable to obtain tissue, we can supplement with liquid biopsy through blood, hydrothorax or ascites, pericardial effusion, cerebrospinal fluid and other specimens (Zhang et al, 2017b).…”
Section: Overview Of Detection Methodsmentioning
confidence: 99%
“…Host genetic may contribute to the development of the diseases [8,9]. The encoding gene of the Mn-SOD enzyme is located on the long arm of chromosome 6q25.2.…”
Section: Introductionmentioning
confidence: 99%